EEG pattern for stress condition during listening rock music and binaural beat sound - Mohamed, N. A. N.; Fuad, N.; Marwan, M. E.; Norazlin, Norazlin (Penerbit UTHM, 2022)
Music has a great effect on human brain and brainwaves. It is already proven that listening to music such as binaural beat sound and rock music increases the beta band power that is associated to increase the stress condition during listening. This research were conducted to determine the EEG pattern for stress condition during listening binaural beat sound and rock music. The research were conducted due to there is no previous research that conduct an experiment related binaural beat during listening. The previous researcher only focus on the effect of binaural beat after the listening. Experiment were conducted on 5 subjects which are 3 female and 2 male and the data of brainwaves of the samples were collected. The data collected were focused only on Alpha band and Beta band which only exist when someone are in awake state. The data were collected by using Emotiv Insight 5-Channel EEG Mobile set which consist of the Emotiv Insight headset, the Universal USB Receiver and the Emotiv Pure EEG software. The data were in power spectral density (PSD) form and it were analyzed by using SPSS software. In SPSS software, the data were analyzed to find the mean, standard deviation and the distribution. From the analysis and discussion, the hypothesis of this research are proven as the beta band are increasing and higher than alpha band. As for the recommendation, the next researcher could increase the number of subject for experimental and the songs also recommended to be divided based on subject song preferences.